Dancing to freedom the true story of Mao's last dancer - Li, Cunxin (Walker & Company, 2008)
Selected by Chairman Mao's officials from among millions of children to become a dancer, Li's new life began as he left his family behind. At the Beijing Dance Academy, days were long and difficult. Li's hard work was rewarded when he was chosen yet again, this time to travel to America. -- A Junior Library Guild selection